(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2022)
The present research, through a systematic documentary analysis, aims to identify and point out the changes that impacted the restorative justice practices in the State of Paraná, before the advent of the Covid-19 pandemic in the period from 2020 to 2021. For this, based on bibliographic and documentary research, a brief exposition of the organization of restorative justice in Brazil and in the State of Paraná was presented in order to contextualize the transformations that have occurred in this context, as well as to indicate the guidelines found for the adequate provision of this service in a virtual way. Therefore, based on the results found, it was possible to verify the challenging and, at the same time, innovative dimension that the virtual environment has provided to the jurisdictional and judicial staff of Paraná.